Descrizione di una Tecnica di Rilievo Fotogrammetrica supportata da un Algoritmo di Intelligenza Artificiale - Santoro, Nicola (Archeomatica, 2019)
Deep Learning has entered strongly into the everyday lives of all of us. We find it in the world of journalism, in the economic sector, in the medical sector and so on. In the world of three-dimensional reality capturing, there are numerous possibilities for implementation. The case study, presented here, starts from the photogrammetric scan of the statue of Dante located at Piazza dei Signori in Verona.